Strategi Pengembangan Ketenagakerjaan Kelompok Penduduk Miskin - Andi Sopandi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2008)
Strategic policy should represent the alignments of government to facilitate the poor that lead to motivated in the making of decision, namely: to apply the life skills that can fullfill the employment opportunities. Therefore, the effective formulation strategies are needed to develop the potential labor force of the poor segment population, mainly intended to solve the problem of ”the limited access that causes poverty.